Risk of schizophrenia in patients with polycystic ovary syndrome: a nationwide population-based cohort study from Taiwan. (2nd October 2021) - Chen, Shih-Fen; Yang, Yu-Cih; Hsu, Chung-Y; Shen, Yu-Chih
Abstract: Objectives: To investigate whether patients with polycystic ovary syndrome (PCOS) are at increased risk for incident schizophrenia and whether PCOS treatment (clomiphene, cyproterone, or metformin) affects the incidence of schizophrenia. Methods: An overall of 7146 PCOS patients and 28, 580 non-PCOS controls matched by age, index year, and Charlson Comorbidity Index (CCI) score were included between 2000 and 2012 and followed up until 2013 using a validated nationally representative sample from Taiwan. Participants newly diagnosed as schizophrenia were defined as incidents. Cox regression analysis was used to calculate the hazard ratio (HR) with a 95% confidence interval (CI) of the schizophrenia incidence rate between the two studied groups. Results: PCOS patients were at increased risk of incident schizophrenia compared to non-PCOS controls after adjusting for age, CCI score, comorbidities, and different treatment options (0.49 versus 0.09 per 1000 person-years, HR: 6.93, 95% CI: 3.25–14.7). After adjusting for above-mentioned covariates, metformin treatment had a protective effect against the incident schizophrenia compared to non-users (HR: 0.16, 95% CI: 0.06–0.41). Also, treatment with clomiphene and cyproterone had only a limited impact on the incident schizophrenia. Conclusion: This study shows PCOS patients are at increased risk of incident schizophrenia, and the metformin treatment has a protective effect against incident schizophrenia.